Identification of domains for Malaysian university staff happiness index development - Md. Yassin, Sulaiman (Canadian Center of Science and Education, 2014)
Without any doubt happiness among staff in any organization is pertinent to ensure continued growth and development. However, not many studies were carried out to determine the domains that will be able to measure the level of happiness among staff in universities. Thus, the aim of this study is to elicit the domains that explain the overall happiness index among university staff. A qualitative method using the Nominal Group Technique was employed to collect data from five clusters in a research university in Malaysia. The findings revealed a number of domains and sub-domains that will assist in the development of a happiness index. It is believed that this study will be useful for universities to examine on the level of happiness index in their respective universities.